Translation into Spanish, Transcultural Adaptation and Validation of the Foot Function Index Revised Short Form (FFI_RSF) Questionnaire - Cervera-Garvi, Pablo; Ortiz-Romero, Mercedes; Gordillo-Fernández, Luis; García-Payá, Irene; Ortega-Ávila, Ana Belén; Díaz-Miguel, Salvador Francisco (MDPI, 2025)
Background/Objectives: This study aimed to translate the Foot Function Index Revised Short Form (FFI RSF-Sp) into Spanish, perform a transcultural adaptation, and validate the resulting questionnaire on foot and ankle function. The revised instrument, derived from the original version of the FFI, incorporates additional subscales on ankle stiffness and overall quality of life that help produce a more comprehensive assessment and overcome some limitations. Methods: The final sample consisted of 306 participants from Malaga and Seville (Spain), all aged over 18 years and native Spanish speakers. These participants also completed the FAAM-Sp and VASFA-Sp validated questionnaires. The measurement properties of FFI RSF-Sp were evaluated in accordance with the Consensus-Based Standards for the Selection of Health Status Measurements Instruments (COSMIN) recommendations. Results: Factor analysis confirmed the existence of a five-factor structure, explaining 67.6% of the total variance, with an RMSEA of 0.0785 and a Tucker–Lewis index of 0.874. Internal consistency was excellent, with an overall Cronbach’s alpha of 0.963 and subscale values ranging from 0.776 to 0.886. Furthermore, moderate to strong correlations were obtained with the VASFA-Sp (r = −0.651) and FAAM ADL (r = −0.737, p < 0.001), and the obtained area under the curve value was 0.806 (p < 0.001), confirming the discriminatory capacity of the instrument. Conclusions: The FFI RSF-Sp is a valid, reliable, and sensitive instrument for assessing foot and ankle function in a Spanish-speaking population. The incorporation of additional dimensions improves the understanding of dysfunction, and the robust psychometric indicators of this questionnaire make it appropriate for use in clinical and research settings, facilitating the detection of functional alterations and enhancing treatment follow up. Keywords: foot; ankle; function; transcultural; validity; questionnaire properties
Keywords: Pies - Lesiones y heridas - Test; Foot; Ankle; Function; Transcultural; Validity; Questionnaire properties